LEADING MOTIVES FOR ENGAGEMENT IN SPORTS REHABILITATION AMONG MILITARY VETERANS (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The article is devoted to the analysis of an empirical study focused on the specifics of motivation for sports rehabilitation among military veterans. The purpose of the article was to identify the leading motives for engaging in sports, the characteristics of internal and external motives, and the reasons for amotivation toward sports.Methods. 91 military veterans of the Security and Defense Forces of Ukraine (81 men, 10 women) were involved. Qualitative and quantitative diagnostic methods were used: questionnaires, interviews, and the Sports Motivation Scale (SMS-28) test, with data analyzed using applied thematic analysis.Results. The presented results of the study indicate the need for special measures to explain and promote sports rehabilitation among military veterans at all stages of the rehabilitation process. An important component of this work is considering the psychological characteristics of the motivation structure for sports activity in veterans. Motivation to gain a "window of new opportunities" through participation in sports, physical and mental well-being, social connections, prevention of self-isolation, and an active role in family and social life are strong motivators influencing veterans' mindset. At the same time, the study revealed pronounced amotivational components, indicating confusion, insecurity, and a lack of desire to achieve high results in sports. This may be due to viewing sports as a "means for restoring physical and mental resources" rather than for "sporting success," which is more typical among "civilian" athletes. This perspective results in a lack of confidence in one's capabilities, limited prospects for a sports career, and doubts about combining military service with athletic activity.Conclusions. The study found that internal motives prevail in the structure of sports motivation, with leading ones including the desire to improve physical and mental health, opportunities for self-development, and restoring the ability to lead an active social life. For those with predominantly internal motivation, sport is seen as a "new life experience," a way to increase self-esteem, and an important part of life beyond official duties. Among external motives, key drivers include meeting the expectations of others, likely linked to social perceptions of the "military figure" as resilient, strong, and fit. Although some veterans are motivated by athletic achievement and the chance to join national or international sports teams, these were not found to be dominant motives.
Keywords: combatant; external and internal motives; military veteran; motivation; sport; sports rehabilitation; Invictus Games; amotivation